Emotionalism following brain damage: a complex phenomenon. Issue 780 (October 1990) - Allman, P.; Hope, R. A.; Fairburn, C. G.
Abstract : Emotionalism is a common and distressing consequence of many forms of brain damage. There is uncertainty about its classification, aetiology and treatment. A commonly used typology is difficult to apply in practice as illustrated by three clinical examples. We describe the various components of emotionalism and highlight their range and variability. In future research each component should be examined in detail using a standardized form of assessment.